A ruthenium-based 5-fluorouracil complex with enhanced cytotoxicity and apoptosis induction action in HCT116 cells - Valdenizia Rodrigues Silva (Nature Portfolio, 2018)
Abstract Combination of multifunctionalities into one compound is a rational strategy in medicinal chemical design, and have often been used with metallodrug-based compounds. In the present study, we synthesized a novel ruthenium-based 5-fluorouracil complex [Ru(5-FU)(PPh3)2(bipy)]PF6 (PPh3 = triphenylphosphine; and bipy = 2,2′-bipyridine) with enhanced cytotoxicity in different cancer cells, and assessed its apoptosis induction action in human colon carcinoma HCT116 cells. The complex was characterized by infrared, cyclic voltammetry, molar conductance measurements, elemental analysis, NMR experiments and X-ray crystallographic analysis. In both 2D and 3D cell culture models, the complex presented cytotoxicity to cancer cells more potent than 5-FU. A typical morphology of apoptotic cell death, increased internucleosomal DNA fragmentation, without cell membrane permeability, loss of the mitochondrial transmembrane potential, increased phosphatidylserine externalization and caspase-3 activation were observed in complex-treated HCT116 cells. Moreover, the pre-treatment with Z-DEVD-FMK, a caspase-3 inhibitor, reduced the apoptosis induced by the complex, indicating cell death by apoptosis through caspase-dependent and mitochondrial intrinsic pathways. The complex failed to induce reactive oxygen species production and DNA intercalation. In conclusion, the novel complex displays enhanced cytotoxicity to different cancer cells, and is able to induce caspase-mediated apoptosis in HCT116 cells.